The Effectiveness of Cognitive Behavioral Therapy Group Counseling to Reduce Phubbing and Improve Students Interpersonal Communication (Universitas Negeri Semarang, 2020)
The increasing use of smartphones for students surely has an impact on the pattern of social relations. Therefore, this study aimed to prove that cognitive behavioral therapy group counseling is effective to reduce phubbing and improve students’ interpersonal communication. This study used randomized pretest – posttest control group design and involved 16 subjects previously selected by using purposive sampling. To collect the data, this study used Generic Scale of Phubbing (GSP) and Interpersonal Communication Scale (ICS). The result of Mancova test showed that cognitive behavioral therapy was positively effective to reduce phubbing (F (1.12) = 42.89, p < 0.01) and improve interpersonal communication (F(1.12) = 53.11, p < 0.01). The findings of this study proved that there found CBT effects on phubbing and students’ interpersonal communication